Models to explain fatigue during prolonged endurance cycling - Abbiss, C. R.; Laursen, P. B. (Sports Medicine, 2005)
Much of the previous research into understanding fatigue during prolonged cycling has found that cycling performance may be limited by numerous physiological, biomechanical, environmental, mechanical and psychological factors. From over 2000 manuscripts addressing the topic of fatigue, a number of diverse cause-and-effect models have been developed. These include the following models: (i) cardiovascular/anaerobic; (ii) energy supply/energy depletion; (iii) neuromuscular fatigue; (iv) muscle trauma; (v) biomechanical; (vi) thermoregulatory; (vii) psychological/motivational; and (viii) central governor. More recently, however, a complex systems model of fatigue has been proposed, whereby these aforementioned linear models provide afferent feedback that is integrated by a central governor into our unconscious perception of fatigue. This review outlines the more conventional linear models of fatigue and addresses specifically how these may influence the development of fatigue during cycling. The review concludes by showing how these linear models of fatigue might be integrated into a more recently proposed nonlinear complex systems model of exercise-induced fatigue.